Laminate manufacturing method
The use of a silane coupling agent in conjunction with dry plating enhances adhesion between resin and metal layers in three-dimensional circuit components, addressing adhesion challenges and enabling high-frequency, high-density laminates without surface roughening.
Patent Information
- Application Number
- JP2024106501
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-30
- Filing Date
- 2024-07-01
- Publication Date
- 2025-01-20
AI Technical Summary
Existing methods for manufacturing three-dimensional molded circuit components with high frequency characteristics and high density face challenges in achieving adhesion between resin and metal layers without surface roughening, which can cause signal loss and heat generation, and are hindered by limitations in plasma treatment and surface modification techniques.
A method involving the use of a silane coupling agent to treat the resin surface, followed by dry plating, specifically sputtering, to enhance adhesion between the resin and metal layer without requiring surface roughening, utilizing plasma, acid, or base treatments to modify the surface hydrophilicity and incorporating a silane coupling agent with a 6-membered aromatic ring and resin-reactive functional groups.
This method results in a laminate with excellent adhesion between the resin and metal layer, enabling high-frequency characteristics and high density without surface roughening, and allows for controlled metal layer formation.
Smart Images

Figure 2025010075000001 
Figure 2025010075000002 
Figure 2025010075000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a laminate including a substrate made of a resin-containing composition and a metal layer provided on the substrate, and in particular to a method for producing a laminate having excellent adhesion between the substrate and the metal layer. [Background technology]
[0002] In recent years, there has been an increasing demand for MIDs (Molded Interconnect Devices), which are three-dimensionally formed conductive wiring on the surface of molded inorganic or polymeric materials. Examples of three-dimensionally molded circuit components include circuit boards for electronic devices and vehicle components with metal plating on acrylonitrile butadiene styrene (ABS) resin.
[0003] Since three-dimensional molded circuit components are composite materials in which different materials are bonded, the adhesion between the different materials is an important characteristic, and improvements have been attempted to improve the adhesion. For example, as a method for improving adhesion, a method has been proposed in which the surface of the substrate is roughened to form fine irregularities, and conductor wiring is then formed thereon (for example, Patent Document 1). However, the irregularities on the substrate surface cause signal transmission loss and heat generation, which impede high-frequency characteristics, and also make it difficult to form fine patterns of conductor wiring, making it difficult to achieve high density. In recent years, there has been an increasing demand for high frequency characteristics and high density for MIDs, and there is a demand for a smooth substrate surface with good adhesion.
[0004] To address the above problem, for example, a technique for improving adhesion without roughening the surface of a substrate is known in which the substrate is irradiated with plasma such as O2 to introduce functional groups onto the surface, thereby modifying the substrate surface. However, the number of functional groups introduced in the plasma treatment is small, and there is a limit to how much adhesion can be improved by plasma treatment alone.
[0005] As another example of a technique for improving adhesion to other materials without roughening the surface of a substrate, a method has been proposed in which a compound capable of imparting reactivity (reactivity imparting compound) is provided to the surface of the substrate (for example, Patent Document 2). Such a reactivity imparting compound has an alkoxysilyl group that generates a silanol group upon hydrolysis, and a functional group such as a diazomethyl group that can react with a resin, and when such a reactivity imparting compound is reacted with a resin, an alkoxysilyl group (or a silanol group generated by hydrolysis) is imparted to the surface of the resin. It is known that such an alkoxysilyl group (or a silanol group) can support a catalyst in electroless plating, and therefore can improve adhesion between a thin copper film formed by electroless plating (and further electrolytic plating) and a resin. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2001-230524 A [Patent Document 2] JP 2020-143007 A Summary of the Invention [Problem to be solved by the invention]
[0007] For three-dimensional molded circuit components that require high frequency characteristics and high density, the mainstream method is to form a thin metal film on the surface of a resin substrate using wet plating (electroless plating, electrolytic plating). However, wet plating can pose significant challenges in terms of managing the processing solution and wastewater after processing. In addition, electrolytic plating has issues such as difficulty in controlling film thickness and forming complex shapes, while electrolytic plating does not have these issues, but it does have the issue of time-consuming processing. In contrast, dry plating has the advantage of being easy to control the formation of the metal layer, but there is an issue with the adhesion between the substrate (resin) and the metal layer, and a method for improving adhesion without the need to roughen the substrate surface has been desired.
[0008] The present invention has been made in consideration of the above problems, and aims to provide a method for producing a laminate having excellent adhesion between a resin substrate and a metal layer in dry plating, without requiring roughening of the substrate surface. [Means for solving the problem]
[0009] The present inventors have conducted research to solve the above problems, and have unexpectedly found that a silane coupling agent used to support a catalyst in electroless plating improves the adhesion between a metal layer formed by dry plating and a resin substrate, thereby completing the present invention. Specifically, the present invention is as follows.
[0010] [1] A method for producing a laminate including a substrate made of a resin-containing composition and a metal layer provided on the substrate, comprising: A step of treating a surface of the substrate with a silane coupling agent; forming the metal layer by dry plating on the surface treated with the silane coupling agent; A method for manufacturing a laminate comprising the steps of: [2] The method for producing a laminate according to [1], wherein the dry plating is a sputtering method. [3] The method includes a step of modifying a surface of the substrate by at least one of a plasma treatment, an acid treatment, and a base treatment; The method for producing a laminate according to [1], further comprising the steps of: treating the surface with a silane coupling agent after modifying the surface. [4] The method for producing a laminate according to [1], wherein the silane coupling agent has an aromatic six-membered ring, one or two alkoxysilyl groups, and one or two resin-reactive functional groups in the molecule. [5] The method for producing a laminate according to [4], wherein the aromatic six-membered ring is a triazine ring. Effect of the Invention
[0011] According to the manufacturing method of the present invention, a laminate having excellent adhesion between a resin substrate and a metal layer can be manufactured without requiring roughening of the substrate surface in dry plating. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described. A method for producing a laminate according to one embodiment of the present invention is a method for producing a laminate comprising a substrate made of a resin-containing composition and a metal layer provided on the substrate, the method comprising: a step of treating a surface of the substrate with a silane coupling agent; and a step of forming a metal layer by dry plating on the surface treated with the silane coupling agent.
[0013] (base material) The substrate used in this embodiment is made of a composition containing a resin. The resin is not particularly limited, but examples thereof include: Thermosetting resins such as epoxy resins, phenolic resins, melamine resins, and silicone resins; Engineering plastics such as polyacetal (POM), polyamide (PA), polycarbonate (PC), modified polyphenylene ether (m-PPE), polybutylene terephthalate (PBT), etc.; Super engineering plastics such as amorphous polyarylate (PAR), polysulfone (PSF), polyethersulfone (PES), polyphenylene sulfide (PPS), polyetheretherketone (PEEK), polyimide (PI), polyetherimide (PEI), liquid crystal polymer (LCP); Suitable examples of these resins include: These resins may be used alone or in combination of two or more.
[0014] In this specification, "engineering plastics" refers to plastics having a deflection temperature under load of 100°C or more as measured according to the ASTM D648 standard, a tensile strength of 49 MPa or more as measured according to the ASTM D638 standard, and a flexural modulus of elasticity of 2.4 GPa or more as measured according to the ASTM D790 standard. In addition, in this specification, "super engineering plastic" refers to an engineering plastic with a continuous use temperature of 150° C. or higher. Here, the continuous use temperature is the heat resistance standard stipulated in the UL standard UL746B, and refers to the temperature at which the physical properties deteriorate by 50% from their initial values when left in the atmosphere at a constant temperature for 40,000 hours.
[0015] The content of the resin in the resin-containing composition can be, for example, 50 mass % or more, 70 mass % or more, 90 mass % or more, or 95 mass % or more.
[0016] The resin-containing composition constituting the substrate may further contain other components such as a filler, an antioxidant, a heat stabilizer, an ultraviolet absorber, a coloring inhibitor, a plasticizer, a flame retardant, a plasticizer, a release agent, an antistatic agent, and a colorant, in addition to the above-mentioned resin.
[0017] The shape of the substrate is not particularly limited, and may be a film, a plate (resin substrate), a three-dimensional molded product, or a multilayer structure thereof.
[0018] (Surface modification process) This embodiment may include a step of modifying the surface of the substrate to be hydrophilic. Some resins contained in the substrate, particularly super engineering plastics, have low hydrophilicity. In this case, the hydrophilicity of the substrate surface is also low, and depending on the treatment method of the silane coupling agent described later, the efficiency of the treatment may be low. In such a case, the treatment efficiency of the silane coupling agent can be improved by providing a process of modifying the substrate surface to be hydrophilic.
[0019] Examples of methods for modifying the surface of a substrate include plasma treatment in which the substrate is irradiated with O2 plasma, atmospheric plasma, N2 plasma, Ar plasma, etc.; acid treatment in which the substrate is immersed in an acid solution; and base treatment in which the substrate is immersed in a base solution. Among these, from the viewpoint of modifying the surface of the substrate without impairing its smoothness, O2 plasma treatment and atmospheric plasma treatment are preferred.
[0020] The conditions for O2 plasma treatment may be, for example, 5 to 40 sccm and 0.5 to 30 minutes.
[0021] (Silane coupling agent) The silane coupling agent used in the present embodiment is a compound having an alkoxysilyl group or a silanol group and a resin-reactive functional group in the molecule, and is typically represented by the following general formula (1). R 1 n (R 2 O) 3-n Si-LX··(1) In formula (1), R 1 is a C1-6 alkyl group; R 2 represents H, a C1-6 alkyl group or a C1-6 alkoxy C1-6 alkyl group; X represents a resin-reactive functional group; L represents a linking group; and n is 0, 1 or 2.
[0022] The compound represented by the above formula (1) is -SiR 1 n (OR 2 ) 3-n The compound represented by the formula (1) includes a compound having a plurality of resin-reactive functional groups in the molecule.
[0023] The alkoxysilyl group in the above formula (1) (-SiR 1 n (OR 2 ) 3-n ;R 2 A C1-6 alkyl group or a C1-6 alkoxy C1-6 alkyl group) generates a silanol group upon hydrolysis. In the above formula (1), R 1 is preferably a methyl group; R 2 is preferably a methyl group, an ethyl group or a 2-methoxyethyl group; n is preferably 0.
[0024] The resin-reactive functional group is a functional group that can react with a resin to form a covalent bond. Examples of such functional groups include amino groups (-NH2), vinyl groups (-CH=CH2), (meth)acryloxy groups (-OCOCH=CH2 or -OCOC(CH3)=CH2), isocyanate groups (-N=C=O), diazomethyl groups (-CHN2), azide groups (-N3), mercapto groups (-SH), ureido groups (-NHCONH2), glycidoxy groups (-OCH2CHOCH2), and epoxy groups (-CHOCH2). These resin-reactive functional groups may form salts.
[0025] The linking group is any group that links an alkoxysilyl group or a silanol group with a resin reactive functional group.
[0026] Preferred examples of the silane coupling agent include 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-metha(acryloxy)propyltriethoxysilane, 3-metha(acryloxy)propylmethyldiethoxysilane, 3-metha(acryloxy)propyltrimethoxysilane, 3-metha(acryloxy)propylmethyldimethoxysilane, 3-isocyanatepropyltriethoxysilane, 3-ureidopropyltrialkoxysilane, and the like.
[0027] Another preferred example of the silane coupling agent is one having an aromatic six-membered ring, one or two alkoxysilyl groups, and one or two resin-reactive functional groups in the molecule. Here, the aromatic six-membered ring is included in the linking group L in the above formula (1). Specific examples of the aromatic 6-membered ring include a benzene ring and a heterocycle such as a triazine ring. A triazine ring is preferable, and a 1,3,5-triazine ring is particularly preferable.
[0028] In addition, in such a silane coupling agent, it is preferable that one or two alkoxysilyl groups and one or two resin-reactive functional groups are linked to the aromatic six-membered ring so as to face each other. Here, "linked to the aromatic six-membered ring so as to face each other" means that the alkoxysilyl group and the resin-reactive functional group are linked to the aromatic six-membered ring as represented by the following general formulas (2) to (5).
[0029] General formula (2): A case in which an alkoxysilyl group of 1 and a resin-reactive functional group of 1 are linked to an aromatic six-membered ring so as to face each other. [ka]
[0030] In formula (2), R 2 is a C1-6 alkyl group or a C1-6 alkoxy C1-6 alkyl group; L 1 and L 2 each independently represents either none or any linking group; R 1 X and n are the same as those in the above formula (1). In the formula (2), the aromatic six-membered ring is shown as a benzene ring, but as described above, the aromatic six-membered ring may be a heterocycle such as a triazine ring.
[0031] General formula (3): A case in which an alkoxysilyl group of 1 and a resin-reactive functional group of 2 are linked to an aromatic six-membered ring so as to face each other. [ka]
[0032] General formula (4): A case in which an alkoxysilyl group of 2 and a resin-reactive functional group of 1 are linked to an aromatic six-membered ring so as to face each other. [ka]
[0033] General formula (5): A case in which an alkoxysilyl group of 2 and a resin-reactive functional group of 2 are linked to an aromatic six-membered ring so as to face each other. [ka]
[0034] The definitions in formulas (3) to (5) are the same as those in formula (2). In the silane coupling agents represented by the general formulas (2) to (5), the alkoxysilyl group and the resin-reactive functional group are linked to an aromatic six-membered ring so that they face each other, and therefore when the resin-reactive functional group is bonded to the surface of the substrate (the resin), the alkoxysilyl group (or the silanol group generated by hydrolysis) is likely to be regularly arranged on the surface of the substrate and is likely to be oriented nearly perpendicular to the substrate. This makes it easier to form a highly smooth metal layer when the metal layer is formed by dry plating, which will be described later.
[0035] The silane coupling agent is more preferably a compound represented by the following general formula (6) or (7).
[0036] [ka]
[0037] [ka]
[0038] In formulas (6) and (7), L 3 -R 3 (R 4 )N- or -R 3 S- and R 3 is bonded to Si, and N or S is bonded to the 1,3,5-triazine ring. 3is a C1-12 hydrocarbon group; R 4 is H, a C1-12 hydrocarbon group, or -R 5 -SiR 1 n (OR 2 ) 3-n and R 5 is a C1-12 hydrocarbon group. X' is a mercapto group, an amino group, a 2-aminoethylamino group (-NH(CH2)2NH2), an azide group or a diazomethyl group, which may form a salt. R 1 , R 2 and n is the same as in formula (2) above.
[0039] Particularly preferred specific examples of such silane coupling agents include the compounds represented by the following formulas (8) to (11): All of these compounds are commercially available from Io Chemical Research Institute.
[0040] Formula (8): N,N'-bis(2-aminoethyl)-6-(3-triethoxysilylpropyl)amino-1,3,5-triazine-2,4-diamine (also known as aTES); [ka]
[0041] Formula (9): 6-(3-triethoxysilylpropylamino)-1,3,5-triazine-2,4-dithiol monosodium salt (also known as nTES); [ka]
[0042] Formula (10): 6-(3-triethoxysilylpropylamino)-1,3,5-triazine-2,4-diazide (also known as pTES); [ka]
[0043] Formula (11): 2,4-bis[(3-triethoxysilylpropyl)amino]-6-diazomethyl-1,3,5-triazine (also referred to as PC1); [ka]
[0044] (Silane coupling agent treatment process) This step is a step of treating the surface of the substrate with the silane coupling agent. The method of treating silane coupling agent is not particularly limited. For example, the method of contacting the substrate with silane coupling agent solution can be mentioned, more specifically, the substrate can be immersed in the silane coupling agent solution, or the silane coupling agent solution can be applied to the substrate. Note that the silane coupling agent solution includes the dispersion liquid in which the silane coupling agent is dispersed, and the same applies below.
[0045] The solvent (including the dispersion medium) used in the silane coupling agent solution is not particularly limited as long as it can dissolve or disperse the silane coupling agent uniformly, but the following can be used: water; alcohols such as methanol, ethanol, isopropanol, ethylene glycol, and diethylene glycol; ketones such as acetone and methyl ethyl ketone; esters such as ethyl acetate; halides such as methylene chloride; olefins such as butane and hexane; ethers such as tetrahydrofuran and butyl ether; aromatics such as benzene and toluene; amides such as dimethylformamide and methylpyrrolidone; etc. Also, a mixed solvent obtained by mixing these various solvents may be used.
[0046] The concentration of the silane coupling agent in the silane coupling agent solution can be, for example, 0.01% by mass to 2% by mass, more preferably 0.03% by mass to 0.5% by mass, and particularly preferably 0.05% by mass to 0.3% by mass. By being in the above range, the substrate surface can be sufficiently coated, and further, since the substrate surface can be coated with one molecule, the coated surface is unlikely to become rough or uneven, and sufficient bonding strength can be easily obtained.
[0047] The silane coupling agent solution may contain various components other than the silane coupling agent, such as a stabilizer, a polymerization inhibitor, and a photodegradation inhibitor.
[0048] When the substrate is immersed in the silane coupling agent solution, the immersion time can be 1 second or more, preferably 30 seconds or more, and more preferably 3 minutes or more. The upper limit of the immersion time is not particularly limited, but can be, for example, 60 minutes or less, and further 10 minutes or less.
[0049] The temperature of the silane coupling agent solution can be, for example, 10 to 60°C, and can further be 15 to 40°C.
[0050] When the resin-reactive functional group in the silane coupling agent is an amino group, an isocyanate group, a mercapto group, a ureido group, a glycidoxy group, an epoxy group, or the like, the bonding reaction between the functional group and the resin can be further promoted by contacting the silane coupling agent solution with the substrate, washing away unreacted silane coupling agent as necessary, and then performing a heat treatment at 80 to 200°C for 1 to 10 minutes.
[0051] In addition, when the resin-reactive functional group in the silane coupling agent is a diazomethyl group, an azide group, a vinyl group, a (meth)acrylic group, etc., the bonding reaction between the functional group and the resin may be promoted by contacting the silane coupling agent solution with the substrate and then irradiating the substrate with light. After the light irradiation, the unreacted silane coupling agent may be washed away as necessary.
[0052] The substrate treated with the silane coupling agent obtained as above can be stored by vacuum packing or the like.
[0053] (Metal layer formation process) This step is a step of forming a metal layer by dry plating on the surface of the substrate that has been treated with the silane coupling agent.
[0054] The method for forming the metal layer is not particularly limited as long as it is a dry plating method, and examples thereof include a sputtering method, a vapor deposition method, and a spray coating method.
[0055] Here, examples of the sputtering method include DC sputtering, RF sputtering, magnetron sputtering, ion beam sputtering, and reactive sputtering. The above sputtering is preferably carried out in a low vacuum (for example, 3 to 0.1 Pa, or preferably 2 to 0.8 Pa).
[0056] Examples of the deposition method include vacuum deposition method, chemical vapor deposition method (CVD method), etc. Examples of the vacuum deposition method include molecular beam epitaxy method (MBE method), physical vapor deposition method (PVD method), etc. Examples of the CVD method include thermal CVD method, catalytic CVD method, photo CVD method, plasma CVD method, laser CVD method, epitaxial CVD method, atomic layer CVD method, organometallic CVD method, chloride CVD method, etc.
[0057] The above dry plating methods may be used alone or in combination of two or more. Among these, the sputtering method is preferred, and it is particularly preferred to perform sputtering in the above low vacuum from the viewpoints of high adhesion that is not easily affected by surface roughness, good adhesion to irregular shapes, low stress, etc.
[0058] Examples of metals constituting the metal layer include Cu, Ag, Au, Pt, Ni, and Cr, and may be alloys of two or more of these. Among these, Cu, Ni, Au, and Cr are preferred.
[0059] In addition, when the substrate treated with the silane coupling agent may contain moisture, gas, etc., it may be subjected to a degassing treatment to remove these, and then subjected to dry plating. Such a degassing treatment may be performed, for example, under low pressure conditions (for example, 2×10 -2 The curing can be carried out by subjecting the substrate to a heat treatment at a pressure of 40 to 120° C. (or less than 100 Pa) for 5 to 120 minutes. In addition, when the substrate is subjected to dry plating after being treated with a silane coupling agent and then stored for a relatively long period of time, a plasma treatment may be performed to activate the molecular bonding agent (especially the silanol group). As the plasma in such a plasma treatment, O2, N2, Ar, etc. can be used, and the treatment can be performed, for example, under low pressure conditions (for example, 50 Pa or less), at 200 to 900 W, for 1 to 20 seconds.
[0060] According to the method of the present embodiment described above, in dry plating, which allows easy control of the formation of a metal layer, it is possible to produce a laminate having excellent adhesion between the substrate (resin) and the metal layer without requiring roughening of the substrate surface.
[0061] The above-described embodiments are described for the purpose of facilitating understanding of the present invention, and are not described for the purpose of limiting the present invention. Therefore, each element disclosed in the above embodiment is intended to include all design modifications and equivalents that fall within the technical scope of the present invention.
[0062] For example, when the metal layer is to be thickened, it is possible to form the metal layer by the dry plating, and then perform an electroplating process to grow the metal film in a short time. The thickness of the metal film after the electroplating process can be appropriately selected and can be, for example, 1 μm to 50 μm. EXAMPLES
[0063] The present invention will be described in more detail below by showing Production Examples, Test Examples, etc., but the present invention is not limited to the following Test Examples, etc.
[0064] [Example 1] <Production Example 1> (material) The substrate used was a three-dimensional substrate made of epoxy resin and measuring 3 cm x 2.9 cm x 0.617 cm (TM-261, manufactured by Nippon Gosei Kako Co., Ltd.) The substrate was subjected to ultrasonic cleaning in an ethanol bath and then thoroughly dried. As the silane coupling agent, 6-(3-triethoxysilylpropylamino)-1,3,5-triazine-2,4-dithiol monosodium salt (nTES, manufactured by Io Chemical Research Institute Co., Ltd.) represented by the following formula (9) was used. nTES was dissolved in distilled water to a concentration of 0.1% by mass.
[0065] [ka]
[0066] (Silane coupling agent treatment) The above substrate was placed in an O2 plasma generator (Diener, PICO POWDER TREATMENT) and subjected to O2 plasma treatment for 3 minutes at 150 W and 20 sccm. The plasma-treated resin substrate was then immersed in the above nTES solution at 25°C for 1 minute.
[0067] Next, the resin substrate was taken out of the nTES solution, washed with distilled water and ethanol in order to remove unreacted nTES, and then dried. Subsequently, the substrate was heated at 120°C for 10 minutes to obtain an nTES-treated substrate. The nTES-treated substrate can be stored by vacuum packing or the like.
[0068] (Sputtering) The nTES-treated substrate was placed under reduced pressure (8 × 10 -4The resin substrate was heated at 100°C for 30 minutes at a pressure of 1.3 Pa or less to remove gases and moisture that may be present in the resin substrate. The obtained substrate was placed in a sputtering device (Shimadzu UHSP-T2040H), the air was evacuated, and the entire substrate was subjected to O2 plasma treatment at 900 W for 10 seconds. Thereafter, sputtering was performed under an Ar atmosphere (1.3 Pa) using Cu as the sputtering target, to obtain a laminate in which a Cu film (thickness: 0.3 μm) was formed on the surface of the substrate.
[0069] (Electrolytic plating) In order to measure the peel strength of the laminate, electrolytic plating with Cu was further carried out. The electrolytic Cu plating solution used was a CuSO4 / H2SO4 aqueous solution (CuSO4 concentration: 60 g / L). The electrolytic Cu plating conditions were 0.12 A: 600 seconds (10% of the area) → 0.24 A: 600 seconds (20% of the area) → 1.22 A: 2400 seconds (100% of the area), and the thickness of the Cu film was increased to 43 μm.
[0070] After the electrolytic Cu plating treatment, the laminate was washed with water and ethanol, respectively, and thoroughly dried. Then, a heat treatment was performed at 80°C for 10 minutes, then 150°C for 10 minutes, and finally 200°C for 10 minutes to obtain a laminate (sample 1) for peel strength measurement.
[0071] <Production Example 2> The same procedure as in Production Example 1 was carried out except that in the silane coupling agent treatment, the substrate was immersed in the nTES solution for 5 minutes, to obtain a laminate (sample 2) for measuring peel strength.
[0072] <Production Example 3> The same procedure was carried out as in Production Example 1, except that the plasma treatment and immersion in the nTES solution were not carried out, to obtain a laminate (sample 3) for measuring peel strength.
[0073] <Test Example 1> Grid test The surfaces of the laminates (samples 1 to 3) obtained in the above manufacturing examples on which the Cu film was formed were cut in a checkerboard pattern at intervals of 1.0 mm using a cutter knife. Cellophane tape (Nichiban Co., Ltd., product name: Cellophane Tape (registered trademark)) was applied to the checkerboard-shaped areas, and the cellophane tape was then peeled off to verify whether the metal layer peeled off from the substrate. The results are shown in Table 1.
[0074] <Test Example 2> SAICAS measurement The peel strength of the Cu film of the laminates (samples 1 to 3) obtained in the above manufacturing examples was measured using the SAICAS (Surface and Interfacial Cutting Analysis System) method. For the SAICAS method, a SAICAS NN-05 device manufactured by Daipla Wintes was used, and measurements were performed under the following conditions. The results are shown in Table 1.
[0075] =SAICAS condition= Uses diamond cutting edge (cutting edge width 1mm, C.DIA) Diamond blade Rake angle = 10° Clearance angle = 20° Blade width = 1mm Vertical speed=0.2μm / sec, horizontal speed=2μm / sec Shear angle=45°
[0076] [Table 1]
[0077] <Result> As shown in Table 1, it was confirmed that Samples 1 and 2, which were treated with the nTES solution, had improved peel strength compared to Sample 3, which was not treated with the nTES solution.
[0078] [Example 2] <Production Example 4> (material) The substrate used was a three-dimensional substrate made of epoxy resin and measuring 3 cm x 2.9 cm x 0.617 cm (TM-261, manufactured by Nippon Gosei Kako Co., Ltd.) The substrate was subjected to ultrasonic cleaning in an ethanol bath and then thoroughly dried. The silane coupling agent used was the above-mentioned 6-(3-triethoxysilylpropylamino)-1,3,5-triazine-2,4-dithiol monosodium salt (nTES, manufactured by Io Chemical Research Institute Co., Ltd.) nTES was dissolved in distilled water to a concentration of 0.1% by mass.
[0079] (Silane coupling agent treatment) The above substrate was placed in an O2 plasma generator (Diener, PICO POWDER TREATMENT) and subjected to O2 plasma treatment for 3 minutes at 150 W and 20 sccm. The plasma-treated resin substrate was then immersed in the above nTES solution at 25°C for 1 minute.
[0080] Next, the resin substrate was taken out of the nTES solution, washed with distilled water and ethanol in order to remove unreacted nTES, and then dried. Subsequently, the substrate was heated at 120°C for 10 minutes to obtain an nTES-treated substrate. The nTES-treated substrate can be stored by vacuum packing or the like.
[0081] (Sputtering) The nTES-treated substrate was placed under reduced pressure (8 × 10 -4 The resin substrate was heated at 100°C for 30 minutes at a pressure of 1.3 Pa or less to remove gases and moisture that may be present in the resin substrate. The obtained substrate was placed in a sputtering device (Shimadzu UHSP-T2040H), the air was evacuated, and the entire substrate was subjected to O2 plasma treatment at 900 W for 10 seconds. Thereafter, sputtering was performed under an Ar atmosphere (1.3 Pa) using Cu as the sputtering target, to obtain a laminate in which a Cu film (thickness: 0.3 μm) was formed on the surface of the substrate.
[0082] (Electrolytic plating) In order to measure the peel strength of the laminate, electrolytic plating with Cu was further carried out. The electrolytic Cu plating solution used was a CuSO4 / H2SO4 aqueous solution (CuSO4 concentration: 60 g / L). The electrolytic Cu plating conditions were 0.12 A: 600 seconds (10% of the area) → 0.24 A: 600 seconds (20% of the area) → 1.22 A: 2400 seconds (100% of the area), and the thickness of the Cu film was increased to 43 μm.
[0083] After the electrolytic Cu plating treatment, the laminate was washed with water and ethanol, respectively, and thoroughly dried. Then, a heat treatment was performed at 80°C for 10 minutes, then 150°C for 10 minutes, and finally 200°C for 10 minutes to obtain a laminate (sample 4) for peel strength measurement.
[0084] <Production Example 5> In the silane coupling agent treatment, the same procedure as in Production Example 4 was carried out except that the nTES solution was changed to a 0.1 mass% aqueous solution of 3-aminopropyltriethoxysilane (APTES, manufactured by Aldrich Chemistry) to obtain a laminate (Sample 5) for peel strength measurement.
[0085] <Production Example 6> The same procedure as in Production Example 4 was repeated, except that in the silane coupling agent treatment, the nTES solution was changed to a 0.1 mass% aqueous solution of 3-mercaptopropyltriethoxysilane (MPTES, manufactured by Tokyo Chemical Industry Co., Ltd.), to obtain a laminate (sample 6) for peel strength measurement.
[0086] <Production Example 7> The same procedure as in Production Example 4 was repeated, except that in the silane coupling agent treatment, the nTES solution was changed to a 0.1 mass% aqueous solution of 3-glycidoxypropyltriethoxysilane (GPTES, manufactured by Shin-Etsu Chemical Co., Ltd.), to obtain a laminate (Sample 7) for peel strength measurement.
[0087] <Production Example 8> A laminate for measuring peel strength (sample 8) was obtained in the same manner as in Production Example 4, except that in the silane coupling agent treatment, the nTES solution was changed to distilled water.
[0088] <Test Example 3> SAICAS measurement The peel strength of the Cu film was measured for the laminates (samples 4 to 7) obtained in the above manufacturing examples using the SAICAS (Surface and Interfacial Cutting Analysis System) method. For the SAICAS method, a SAICAS NN-05, a device manufactured by Daipla Wintes, was used under the following conditions. For the measurement of each sample, three samples were manufactured for each manufacturing example, and measurements were taken at four points for each sample, with the average value being the measurement result. The results are shown in Table 2. In addition, for the laminate obtained in Production Example 8 (Sample 8), the Cu film was not sufficiently adhered to the base resin, and measurement by the SAICAS method was not possible, so in Table 2 it is shown as 0 kN / m (measurable).
[0089] =SAICAS condition= Uses diamond cutting edge (cutting edge width 0.1mm, C.DIA) Diamond blade Rake angle = 10° Clearance angle = 20° Blade width = 1mm Vertical speed=0.5nm / sec, horizontal speed=100nm / sec Shear angle=45°
[0090] [Table 2]
[0091] <Result> As shown in Table 2, the peel strength was significantly improved by treating with a silane coupling agent, and among them, nTES treatment was the most excellent.
Claims
1. A method for producing a laminate including a substrate made of a resin-containing composition and a metal layer provided on the substrate, comprising the steps of: A step of treating a surface of the substrate with a silane coupling agent; forming the metal layer by dry plating on the surface treated with the silane coupling agent; A method for manufacturing a laminate comprising the steps of:
2. The method for producing a laminate according to claim 1 , wherein the dry plating is a sputtering method.
3. The method includes modifying a surface of the substrate by at least one of a plasma treatment, an acid treatment, and a base treatment; The method for producing a laminate according to claim 1 , further comprising the step of treating the surface with the silane coupling agent after modifying the surface.
4. 2. The method for producing a laminate according to claim 1, wherein the silane coupling agent has an aromatic six-membered ring, one or two alkoxysilyl groups, and one or two resin-reactive functional groups in the molecule.
5. The method for producing a laminate according to claim 4 , wherein the aromatic six-membered ring is a triazine ring.
Citation Information
Patent Citations
Method of manufacturing three-dimensional molding circuit board
JP2001230524A
Reactivity-imparting compound, manufacturing method thereof, surface reactive solid using reactivity-imparting compound, and method for manufacturing surface reactive solid
JP2020143007A